Implementación de buenas prácticas de manufactura según la normativa técnica ARCSA - DE -067 -2015 -GGG en el taller artesanal " Tierra Linda". - Vargas Ortiz, Tatiana Monserrath (2021)
The present work was developed in the "Tierra Linda" craft workshop where it began with an initial check list for its evaluation of the percentage of compliance with the ARCSA -DE - 067 - 2015 - GGG Regulation, later for the implementation of Good Manufacturing Practices. . In the production processes, it allowed taking preventive measures and general hygiene practices in the handling, preparation, processing, packaging and storage of food for human consumption, in order to guarantee that food is manufactured in adequate sanitary conditions and thus reduces the risks. potential or dangers for its innocuousness. The proposed study is presented as a non-experimental investigation and adopts a proposal and advanced technology modality, applying tools such as observation and documentary review according to the needs of the "Tierra Linda" craft workshop, through standardized operating procedures, the elaboration of the procedures manual, instructions, training schedule, records and control points in the productive elaboration.